Malaysian publication contributions to the field of library and information science / Norhazwani Yazit - Norhazwani, Yazi (2007)
This study uses the bibliometric method to analyse Malaysian publication contributions in the field of library and information science (LIS) from 1965 to 2005. Specifically, this study aims to ascertain the total spread of publications, active Malaysian authors and its authorship patterns, the productive institutions, main channels of research publications, and subject distributions of publications contributed by Malaysian authors in this field. The sample comprises 1045 publications, in the form of 511 (48.9%) journal articles, 474 (45.4%) conference papers, 31 (2.9%) books and 29 (2.8%) book chapters contributed by Malaysian authors in the field of LIS from 1965 to 2005. The publication productivity of Malaysian authors showed a continual growth since 1965 until 2005. The most productive period by Malaysian contributors was during 1995 to 1999. The yearly output of publications by Malaysian authors indicated a gentle upward trend with an average of 25.5 publications per year and it is expected to continue in the future. A total of 506 Malaysian authors contributed to the 1045 publications in the field of LIS during 1965 to 2005. Single-authorship was the dominant authorship patterns but the number of multi-authored works is gradually increasing each year. The results showed that the top three productive institutions in LIS research are Perpustakaan Negara Malaysia, Universiti Malaya Library and Universiti Malaya. Journals were the primary channel used to communicate research findings by Malaysian researchers and the majority of the researchers prefer to publish in local journals. It was revealed that Management of library and information services is the most active subject areas researched upon by Malaysian researchers, followed by Information services, Collection development, ICT applications in LIS, Information sources, Organization of information, and Legal issues in LIS.